Ensaios sobre a agricultura familiar na Região Nordeste do Brasil: Pluriatividade e diferenças para a agricultura não familiar - Santos, Luís Carlos dos (2021)
This dissertation is composed of two articles, with the objective of the first to identify and analyze the possible determinants of the phenomenon of pluriactivity in rural areas, considering the aspects related to the composition of pluriactive families in the Northeast region of Brazil. For this purpose, the Logit econometric model was used based on data from the continuous National Household Sample Survey (PNAD) of 2019. The main results were that the Northeast region stood out for the type of pluriactive families with 10.44% of the total number of rural Brazilian families, and of this total, male heads represent 84.72%. The Northeast region, despite having the largest number of pluriactive families, has this contingent concentrated in three states: Bahia, Ceará and Maranhão. One observed that the determinants of pluriactivity in the rural Northeast of Brazil are the employing family, the employed family, the gender of the head, race, the age group, the education category, the Federative Unit category and the category of per capita income. Therefore, the work infers to the fact that agricultural families are increasingly becoming pluriactive families or non-agricultural families in all Federation Units. The second article aims to characterize and discuss the profile of agricultural producers and establishments of family farming (AF) and non-family farming (ANF) in Brazil and in the Northeast region. A descriptive analysis methodology was used, using data from Sidra/IBGE for the years 2006 and 2017. It was observed as main results that the number of agricultural establishments in AF decreased in Brazil, in the Northeast and in all its states, the opposite occurs in the ANF. Regarding the profile of the heads of the establishments, most are in the age group of 35 > 45 years, male, with the level of education characterized as not knowing how to read and write, and they do not have access to information and technical assistance. Therefore, the work infers that, as the AF maintains its majority share in the occupation of the workforce, which is predominantly owned by the owner, there is a decrease in the number of agricultural establishments and their production area, reflecting in a loss in production in this category. Thus, when the area of AF establishments is reduced, there is a process of expansion of these activities to the ANF.